ROLE OF FINE NEEDLE ASPIRATION CYTOLOGY IN DIAGNOSIS OF PALPABLE BREAST LESIONS AND THEIR COMPARISON WITH HISTOPATHOLOGY - Khattak, Mohammad Sajjad; Ahmad, Fiaz; Rehman, Khalil Ur (Journal of Ayub Medical College Abbottabad, 2020)
Background: The aim of this study was to compare the diagnostic utility o fine needle aspiration cytology (FNAC) in breast lesion with gold standard of histopathological diagnosis. Methods: This descriptive cross-sectional study was conducted in Pathology department of Bannu Medical College in collaboration with Surgery Department of Khalifa Gul Nawaz Teaching Hospital Bannu as well as other private surgical hospitals of the territory. A total of 88 FNAC of palpable breast lesions were performed and compared with their corresponding histopathological reports. Patients age, location of lesion in breast, and other necessary findings were recorded on predesigned proforma, FNAC performed by using 10 ml syringes. Slides prepared and processed for cytological staining and reported by cytopathologist. Corresponding biopsies were processed for histopathological examination and diagnosis. All female patients of any age with breast lesions were included, and those breast lesions for which no histopathological report was available were excluded. Statistical Package for Social Sciences (SPSS) version 20 was used for calculation of frequencies with percentages and mean with standard deviation. Also, specificity, sensitivity, diagnostic accuracy, positive predictive value and negative predictive value were calculated by using formulas. Results: In this study the mean age was 34.44±21.57 years and age range was from 16 to 80 years. The most common age group was 26-35 years followed by 36-45 years. In this study sensitivity was (83.33%), specificity was (100 %), positive predictive value was (100 %), negative predictive value was (99.27%) and diagnostic accuracy was 99.30%. Conclusion: FNAC breast is an easily approachable, less invasive, cheap, rapid and almost accurate diagnostic tool in the diagnosis of palpable as well as non palpable breast lesions. Keywords: FNAC; Breast lesions; Mastitis; Fibroadenoma; Invasive ductal carcinoma